2020
DOI: 10.1002/jmor.21233
|View full text |Cite
|
Sign up to set email alerts
|

The remarkable larval anatomy of Proceratophrys minuta Napoli, Cruz, Abreu and Del‐Grande, 2011 (Amphibia: Anura: Odontophrynidae)

Abstract: The free living larvae of anurans (i.e., tadpoles) are a key element in the evolution and diversification of this group, and as such, their morphology is an important element to understand the phylogenetic relationships of frogs. However, the lack of data on larval morphology prevents us from fully understanding larval evolution in several lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…For instance, the presence of commissura quadratoorbitalis, this cartilaginous structure bridges the processus muscularis and the processus antorbitalis, and it is present in several clades of frogs. More specifically, it has been consistently reported in leptodactylids (e.g., Larson and de Sá 1998 ; Nascimento et al 2021a , 2022 ), bufonids (e.g., Vera Candioti 2007 ; Haad et al 2014 ), and odontophrynids (e.g., Dias et al 2013 , 2014 ; Dias 2020 ). Dias et al ( 2019 ) suggested that the presence of that commissura could be a synapomorphy of Odontophrynidae but given its presence in several closely related lineages (including Allophrynidae), it could be a synapomorphy of a more inclusive clade, and the absence of it a synapomorphy for Centrolenidae.…”
Section: Tadpole Morphologymentioning
confidence: 86%
See 2 more Smart Citations
“…For instance, the presence of commissura quadratoorbitalis, this cartilaginous structure bridges the processus muscularis and the processus antorbitalis, and it is present in several clades of frogs. More specifically, it has been consistently reported in leptodactylids (e.g., Larson and de Sá 1998 ; Nascimento et al 2021a , 2022 ), bufonids (e.g., Vera Candioti 2007 ; Haad et al 2014 ), and odontophrynids (e.g., Dias et al 2013 , 2014 ; Dias 2020 ). Dias et al ( 2019 ) suggested that the presence of that commissura could be a synapomorphy of Odontophrynidae but given its presence in several closely related lineages (including Allophrynidae), it could be a synapomorphy of a more inclusive clade, and the absence of it a synapomorphy for Centrolenidae.…”
Section: Tadpole Morphologymentioning
confidence: 86%
“…Larval cranium of Allophryne ruthveni is quite similar to that of many leptodactylids (e.g., Larson and de Sá 1998 ; Vera Candioti et al 2007 ), bufonids (e.g., Vera Candioti 2007 ; Aguayo et al 2009 ), and odontophrynids (e.g., Nascimento et al 2013 ; Dias et al 2019 ; Dias 2020 ), and it is very different from that of centrolenids. Whereas centrolenids have an elongated cranium, with thin processus ascendens, enlarged pars articularis quadrati, and lack commissura quadratoorbitalis, A. ruthveni has a compact cranium, with a robust processus ascendens, a not so developed processus articularis.…”
Section: Tadpole Morphologymentioning
confidence: 89%
See 1 more Smart Citation
“…Tadpole biology is an exciting field with prospect for improvement in the future. In the last 20 years we were surprised with the description of several novel, and sometimes bizarre, phenotypes (e.g., Haas et al, 2006, 2014; Rowley et al, 2012; Dias, 2020; Dias et al, 2021; Vera Candioti et al, 2017) as previous unstudied taxa are investigated. Pelodryadinae tadpoles seem to hide uncovered phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Tadpole biology is an exciting field with prospect for improvement in the future. In the last 20 years we were surprised with the description of several novel, and sometimes bizarre, phenotypes (e.g., Haas et al, 2006Haas et al, , 2014Rowley et al, 2012;Dias, 2020;Vera Candioti et al, 2017)…”
Section: Discussionmentioning
confidence: 99%